Edukasi Kesiapsiagaan Petugas Kesehatan dalam Menghadapi Bencana Gempa Bumi dan Tsunami di Kota Padang Tahun 2021 - Afzahul Rahmi; Radian Ilmaskal; Izzatul Mardiah; Andre Fernadi Kusuma (STIKes Alifah Padang, 2022)
Earthquakes and tsunamis are natural forces that cause disasters and cause huge losses. The importance of awareness of preparedness in dealing with disasters is an individual action in protecting themselves from these hazards. Efforts that can be made to increase knowledge of human resources or health workers related to preparedness in tackling natural disasters is to provide formal education, namely education through socialization activities. This educational activity aims to make health workers understand about disasters, instill disaster awareness, actions and behaviors to care for disasters and change the mindset of health workers to create a culture of safety through customs, preparedness and local wisdom of disaster prevention. The method of activity used is lecture and discussion. The implementation of this community service is carried out based on three stages, namely, preparation, implementation and evaluation. The results obtained from this community service are that health workers are enthusiastic in participating in this activity and are satisfied with this service.